(untitled) (Research, Society and Development, 2021)
Introduction: Gestational Diabetes Mellitus, defined by the presence of glucose intolerance during pregnancy and other specific types. However, the existence of two classes is also highlighted, the so-called pre-diabetes and impaired glucose tolerance. These last two types are not characterized as clinical forms, but are inducing factors for the progress of the pathology. General Objective: This study aims to discuss and clarify about Gestational Diabetes Mellitus and as possible, care and complications focused on the northern region, but specified in the state of Amazonas. Methodology: This is an integrative literature review that aims to identify care for nutritional treatment and the importance of monitoring prenatal care correctly. Results and Discussion: The importance of nutritional therapy in patients, focusing on foods from the Amazon region that prevent and reduce blood glucose. Conclusion: Through the literature, the importance of diet, exercise and blood glucose control during treatment was remarkable, since data on drug treatment are still insufficient and controversial.